2018
DOI: 10.1111/iwj.13026
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of venous leg ulcers in primary health care: Incidence and prevalence in a health centre—A time series study (2010‐2014)

Abstract: The aims of the study were to describe and analyse the temporal trend of the prevalence and incidence of venous leg ulcers (VLU) over the years 2010 to 2014, to determine healing times and temporal trends in the study period, and to evaluate related aspects such as the use of the Ankle‐Brachial Pressure Index (ABPI) in a primary care health centre. This was a retrospective study based on a time series (years 2010‐2014) of the prevalence and incidence of VLUs in people aged over 40 years in a primary care centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 17 publications
2
51
1
3
Order By: Relevance
“…Venous leg ulceration is the most extreme manifestation of chronic venous disease, and worldwide prevalence is increasing. Compression therapy has been shown to improve ulcer healing, and 1-year outcomes from the Early Venous Reflux Ablation (EVRA) trial revealed that early endovenous ablation of superficial venous reflux (varicose veins) accelerated healing of venous leg ulcers compared with deferred intervention. Early intervention was also shown to be cost-effective in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…Venous leg ulceration is the most extreme manifestation of chronic venous disease, and worldwide prevalence is increasing. Compression therapy has been shown to improve ulcer healing, and 1-year outcomes from the Early Venous Reflux Ablation (EVRA) trial revealed that early endovenous ablation of superficial venous reflux (varicose veins) accelerated healing of venous leg ulcers compared with deferred intervention. Early intervention was also shown to be cost-effective in the short term.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-cultural research study in three outpatient clinics in western Switzerland was conducted following 1 translation of the original instrument into Swiss French by two independent translators, 2 construction of a consensus version based on both translations, 3 two independent back translations of the consensus version into English, 4 review by an expert committee and construction of a draft questionnaire, 5 testing of the draft questionnaire on people with a venous leg ulcer and 6 construction of the final questionnaire version.…”
Section: Method/resultsmentioning
confidence: 99%
“…The occurrence ranges between 0.8 and 2.2 per 1000 people/year. 1 Healing times of VLUs are long, and up to 70% of the patients suffer a recurrence within three months after wound closure. [2][3][4] These wounds have a negative impact on all aspects of daily life.…”
Section: Translation and Cross-cultural Adaptation Of The Venous Leg mentioning
confidence: 99%
“…Many lower limb ulcers are chronic conditions most commonly caused by venous or arterial insufficiency or a combination of both. The prevalence is approximately 0.16% to 1.42% in the adult population but nearly doubles at 1.69% to 5% in those over 65 years of age . In a retrospective time series study in a primary care centre in Barcelona, the incidences of venous leg ulcers have shown an increasing trend, with the rates doubling over a 4‐year period between 2010 and 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is approximately 0.16% to 1.42% in the adult population but nearly doubles at 1.69% to 5% in those over 65 years of age . In a retrospective time series study in a primary care centre in Barcelona, the incidences of venous leg ulcers have shown an increasing trend, with the rates doubling over a 4‐year period between 2010 and 2014 . Those with leg ulceration have a significantly poorer quality of life compared with healthy people, with issues such as pain, poor mobility, and negative psychological functioning .…”
Section: Introductionmentioning
confidence: 99%